Determination of shear strength of high strength reinforced concrete beams: experimental and numerical approach - Rajesh, Cherukupally; Kumar, Garje Rajesh (Journal of Structural Engineering, 2024)
Shear Strength of concrete is one of the important criteria for the analysis and design of structures as it causes thesudden failure and becomes catastrophic. There were several studies on the behavior of shear strength of concretebeams but still there is a scope for further investigation on High Strength Concrete (HSC) beams. In the presentstudy two grades of reinforced concrete beams with three shear span to depth ratios (a/d) 1, 2 and 3 for each gradewere considered. The beams that were cast and tested experimentally were modelled and tested in numerical basedsoftware ATENA. In ATENA, for assigning the material for concrete the cementitious2 and cementitious2 user modelwas considered. The cementitious2 model consists of Euro-code and model-code as default models, both of them wereused in the study to determine the shear strength of reinforced concrete beams. In cementitious2 user material model,the compressive stress-strain model can be user defined in which, the GRK Stress-strain model and Mander’s stressstrainmodel was given as input to find the shear strength of reinforced concrete beams. The shear strength of the testspecimens increased with increasing concrete strength for all a/d ratio values. With the increase in a/d ratio from 1 to3, the shear strength is found to reduce by about 60%. The strains observed in numerical study indicate that the beamshave failed in shear which is similar to experimental results. The shear strength obtained using ATENA with variousmodels was compared with the experimental results and it was found that all the shear strength values were in similarbehaviour with experimental results.